THE SLOTH (Bradypus variegatus Schinz, 1825; Xenarthra; Bradypodidae) IN THE REPORTS AND DESCRIPTIONS OF CHRONICLERS AND NATURALISTS FROM THE 16TH AND 17TH CENTURIES IN BRAZIL - Almeida, Argus Vasconcelos de; Araújo, Ana Isabele de Freitas; Lima, Érica Patrícia de; Santos, Ozias Henrique dos; Silva, Gerlaine Amara da; Soares, Thiago Ferreira (Revista Nordestina de Zoologia, 2011)
The purpose of this study is to analyze the reports and descriptions of the major chroniclers and naturalists about the sloth (Bradypus variegatus Schinz, 1825; Xenarthra; Bradypodidae) in the sixteenth and seventeenth centuries in Brazil and was accomplished through a literature review of the chapters relating to his description in the works of chroniclers and naturalists. Of the Brazilian fauna the animal was one that most caught the attention of chroniclers and European naturalists. We conclude that among the reports stand out from Gabriel Soares de Sousa and Ambrósio Fernandes Brandão (sixteenth century) we see a significant difference between these and the descriptions produced by naturalists Marcgrave and Piso during the Dutch occupation in the Northeast in the seventeenth century. Stands out among naturalists Marcgrave, that approximates the current descriptions of zoological-anatomicals of animal. Piso is an abridged copy of Marcgrave. These historical considerations about the sloth intend to contribute to the acctions of specie conservation.